The effect of dumbbell exercises on smash ability in table tennis sports in men's students class VII SMP Negeri 3 Duhiada`a - Podungge, R.; Amri, M. F. L.; Bumulo, T. (Proceedings of the Unima International Conference on Social Sciences and Humanities (UNICSSH 2022), 2023)
The formulation of the problem in this study is "is there an influence on smash ability in the sport of table tennis through dumbbell exercises in men's students of class VII of Duhiadaa State Junior High School 3?". The purpose of this study is to find out how much influence dumbbell exercises have on smash ability in the sport of table tennis in men's students of class VII of State Junior High School 3 Duhiadaa. The test result obtained tcount = 11,896 ttable values at a = 0.05; dk n-1 (0.05;30-1 = 29) obtained a price of 1.669. Thus tcount is greater than ttabel (tcount = 11,896 > ttabel = 1,669). Based on the test criteria that receive Ha: if tcount > ttable at a = 0.05; n-1, therefore the alternative hypothesis or Ha is acceptable, so it can be stated that there is an influence of dumbbell exercises on the ability of smashes in the sport of table tennis in students of class VII of Duhiadaa State Junior High School 3. Based on the results of the experiments that have been conducted, awarding students significantly in smash ability in the sport of table tennis after the implementation of the experiment. Thus it can be concluded that the author's hypothesis that reads "if dumbbell exercises are applied, then the ability of smash in the sport of table tennis in students of class VII of State Junior High School 3 Duhiadaa will have an effect" is acceptable.